In Originalism's Stead: Old Constitutions and Originalism's Normative Foundations - Loehndorf, Alexander (My University, 2021)
This thesis concerns a philosophical analysis of originalism in a context that has not yet received sufficient attention: in the context of old constitutional regimes. Through this lens, I argue that originalism becomes something lesser in that both the normative justification and legitimacy originalism once held begins to withdraw from the theory’s principled commitments. In other words, the nature of old constitutions begins to reject a normative argument for an originalist approach. The thesis bases this analysis on one originalist theory in particular for the sake of brevity: Lawrence Solum’s public meaning originalism. It proceeds through two avenues of argument: originalism as it relates to 1) historical analysis and the interpretation-construction distinction and 2) stare decisis and democratic legitimacy. Taken together, these avenues point to originalism’s fading normative justification and legitimacy in light of the challenges that old constitutions and their characteristics pose for the judicial philosophy.
Keywords: Originalism, Living Constitutionalism, Constitutional Jurisprudence, Legal Philosophy